Tumor cryoablation in combination with natural killer cells therapy and Herceptin in patients with HER2-overexpressing recurrent breast cancer. (December 2017) - Liang, Shuzhen; Niu, Lizhi; Xu, Kecheng; Wang, Xiaohua; Liang, Yingqing; Zhang, Mingjie; Chen, Jibing; Lin, Mao
Highlights: The combination of cryoablation, NK cells, and Herceptin has good efficacy for HER2 overexpressing recurrent breast cancer. Combinations therapy improves QOL and PFS and reduces CEA, CA15-3, and CTC expression. Combination therapy enhances the immune function of patients. Abstract: In this study, we investigated the clinical benefits of a combination of tumor cryoablation with natural killer (NK) cells therapy and Herceptin for human epidermal growth factor (HER) 2-overexpressing recurrent breast cancer. From May 2015 to May 2016, 48 patients who met the enrollment criteria were assigned to three groups (n = 16): cryoablation group (group I), cryoablation-NK cells therapy group (group II) and cryoablation-NK cells therapy-Herceptin group (group III). Safety and short-term effects were evaluated. All the adverse effects were manageable and acceptable. The three-therapy combination treatment not only yielded good clinical efficacy, it also improved the quality of life; reduced levels of circulating tumor cells (CTCs); reduced carcino-embryonic antigen (CEA) and cancer antigen 15-3 (CA15-3) expression; enhanced immune function significantly. Furthermore, it can resulte in significant prolongation of progression free survival (PFS). This is the first clinical study to demonstrate the benefit of the three-therapy combination of tumor cryoablation, NK cells therapy, and Herceptin for HER2-overexpressing recurrent breast cancer.